2020
DOI: 10.3389/fneur.2020.580408
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Hippocampal Network Connectivity Is Associated With Neurocognitive Dysfunction in Patients With Moderate and Severe Obstructive Sleep Apnea

Abstract: Objectives: This work aims to explore the changes of functional connectivity (FC) within the hippocampus network in patients with moderate and severe obstructive sleep apnea (OSA) and its correlation with neurocognitive dysfunction to explore the potential neurophysiological mechanism.Methods: A total of 32 treatment-naïve patients with moderate or severe OSA and 26 healthy controls (HCs), matched in age, gender, and education, underwent the evaluations of Epworth Sleep Scale, neurocognitive function, full-nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…Zhang et al (2013) discovered impaired FC of the PreCG in OSA patients and confirmed structural and functional disruptions in the anterior DMN containing the SFG, and speculated these damages may be a probable candidate mechanism for cognitive and emotional disorders in patients with OSA. Furthermore, the increase in FC in the temporal gyrus of OSA patients has been associated with neurocognitive impairment, as affirmed by the study of Zhou et al (2020). The brain areas with abnormal FC in our study overlapped with those previously reported to show structural or functional aberrations in OSA, such as the cerebellum, frontal lobe and temporal lobe, which are distributed in the cognitive control circuit along with the dAI and are responsible for memory, attention, language and executive control (Park et al, 2016a;Caporale et al, 2021).…”
Section: Deficits In Functional Connectivity Between the Dorsal Anterior Insula And Cognitive Networksupporting
confidence: 88%
See 1 more Smart Citation
“…Zhang et al (2013) discovered impaired FC of the PreCG in OSA patients and confirmed structural and functional disruptions in the anterior DMN containing the SFG, and speculated these damages may be a probable candidate mechanism for cognitive and emotional disorders in patients with OSA. Furthermore, the increase in FC in the temporal gyrus of OSA patients has been associated with neurocognitive impairment, as affirmed by the study of Zhou et al (2020). The brain areas with abnormal FC in our study overlapped with those previously reported to show structural or functional aberrations in OSA, such as the cerebellum, frontal lobe and temporal lobe, which are distributed in the cognitive control circuit along with the dAI and are responsible for memory, attention, language and executive control (Park et al, 2016a;Caporale et al, 2021).…”
Section: Deficits In Functional Connectivity Between the Dorsal Anterior Insula And Cognitive Networksupporting
confidence: 88%
“…For example, Peng et al (2014) found that higher regional homogeneity (ReHo) occurred in the insula of male patients with severe OSA. In addition, altered limbic-striatalcortical functional connectivity was reported in studies of altered hippocampal resting-state functional networks in OSA (Song et al, 2018;Kang et al, 2020;Zhou et al, 2020). Although ReHo and resting-state functional connectivity (FC) are both based on resting-state fMRI, ReHo, a method for analyzing the coherence and similarities of intraregional spontaneous lowfrequency (0.01-0.08 Hz) signal fluctuations was used to detect unpredicted hemodynamic responses (Zang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“… 48 It has been reported that FC abnormalities in the right hippocampus and right STG and MTG in OSA are negatively correlated with performance of information processing speed, which may probably contribute to the development of cognitive dysfunction. 38 Our previous study found an increase in rs-FC between the left IFG and bilateral ventrolateral amygdala in OSA patients, reflecting the potential adaptive compensation mechanism for the decline in emotion functions. 49 A study reported decreased mean diffusivity and increased functional anisotropy in the temporal lobes and fusiform gyrus, and increased CBF in the ITG was found in OSA with six weeks of CPAP treatment, suggesting that CPAP therapy can recover OSA-induced brain injury.…”
Section: Discussionmentioning
confidence: 82%
“… 37 One functional connectivity study demonstrated decreased functional connectivity between the left cerebellum and hippocampus. 38 Park et al found that OSA showed cerebellar network integration and cerebrocerebellar connectivity was impaired in OSA patients, which may participate in cognitive decline. 39 The cerebellum was susceptible to hypoxia or ischaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired attention is found in OSA children. Studies assessing polysomnograms and MRIs suggest that attention and vigilance are prominent neurocognitive functions that are impaired in children with OSA [ 65 ]. There are three components of attention, each of which can be compromised in patients with OSA.…”
Section: Neurocognitive Abnormalities and Osamentioning
confidence: 99%